2017
DOI: 10.1007/s12325-017-0502-2
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Short-Term Cost-Effectiveness of IDegLira Versus Continued Up-Titration of Insulin Glargine U100 in Patients with Type 2 Diabetes in the USA

Abstract: IntroductionEffective glycemic control can reduce the risk of complications and their related costs in type 2 diabetes mellitus (T2DM). However, many patients fail to reach glycemic targets, often because of adverse effects of treatment (including hypoglycemia or weight gain). The present analysis evaluated the short-term cost-effectiveness of IDegLira versus continued up-titration of insulin glargine U100 in patients with T2DM failing to achieve glycemic control on basal insulin in the US setting.MethodsThe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In clinical practice, therapy intensification for this group of patients would typically be basal insulin initiation; however, our results indicate that addition of IDegLira is a superior treatment option. Furthermore, a previous cost‐effectiveness analysis identified that treatment with IDegLira versus continued uptitration of IGlar U100 demonstrates a lower cost per patient achieving treatment targets . Weight gain and hypoglycaemia are well‐known barriers for insulin initiation for both patients and healthcare providers, therefore IDegLira should be considered at the point of insulin initiation, as patients will have the potential benefits of superior glycaemic control, with lower weight gain and a lower risk of hypoglycaemia, as well as lower perceived treatment burden and easier diabetes management, which could improve treatment compliance and satisfaction .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, therapy intensification for this group of patients would typically be basal insulin initiation; however, our results indicate that addition of IDegLira is a superior treatment option. Furthermore, a previous cost‐effectiveness analysis identified that treatment with IDegLira versus continued uptitration of IGlar U100 demonstrates a lower cost per patient achieving treatment targets . Weight gain and hypoglycaemia are well‐known barriers for insulin initiation for both patients and healthcare providers, therefore IDegLira should be considered at the point of insulin initiation, as patients will have the potential benefits of superior glycaemic control, with lower weight gain and a lower risk of hypoglycaemia, as well as lower perceived treatment burden and easier diabetes management, which could improve treatment compliance and satisfaction .…”
Section: Discussionmentioning
confidence: 99%
“…This study assessed the cost per patient achieving treatment target (cost of control) for various single and composite endpoints for the entire trial population and in patients with baseline HbA1c >8.0% and HbA1c >9.0%. In this study, the significantly greater clinical efficacy of the FRC resulted in lower cost of control values vs continued uptitration of insulin glargine …”
Section: Combination Therapymentioning
confidence: 81%
“…The cost effectiveness of treatment interventions is a key consideration when choosing therapies for people with T2D. Direct comparison of the acquisition costs of different therapies is insufficient to inform healthcare payer decision making as there are multiple factors to consider aside from achieving glycemic control, including the likelihood and burden of adverse events such as hypoglycemia and body weight gain, quality of life, and, importantly, the prognosis for diabetes-related micro-and macrovascular complications [74][75][76].…”
Section: Cost-effectiveness Analysis Of Idegliramentioning
confidence: 99%
“…Short-and long-term cost-effectiveness analyses of IDe-gLira in comparison with uptitration of IGlar U100 and basal-bolus therapy of IGlar U100 and IAsp, have been conducted [74][75][76][77][78][79]. Based on clinical trial data from both the US and the UK, IDegLira has been shown to provide a cost-effective treatment option in people with uncontrolled T2D (Table 3) [74][75][76][77][78][79]. In the analyses where IDegLira was associated with increased costs, incremental costeffectiveness ratios remained well below the US valuebased price benchmark of $100,000-$150,000 per qualityadjusted life-year (QALY) gained suggested by the Institute for Clinical and Economic Review, or the commonly accepted willingness-to-pay threshold of £20,000-£30,000/ QALY in the UK ( Table 3).…”
Section: Cost-effectiveness Analysis Of Idegliramentioning
confidence: 99%
See 1 more Smart Citation